2010
DOI: 10.1111/j.1757-837x.2010.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics of flubendiamide and thiacloprid on tomato (Lycopersicon esculentum Mill) and soil

Abstract: Introduction Flubendiamide, a phthalic acid diamide widely used against the lepidopteran pests and thiacloprid, the first chloronicotinyl insecticide quite effective against the sucking insects, white flies and jassids have recently been used on various vegetable crops in India. Objectives Studies on dissipation kinetics of insecticides is very essential to work out their half‐ lives and waiting periods for the safe consumption of agricultural produce. Methods Standardized methodology support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
2
8
0
Order By: Relevance
“…1). Kooner et al (2010) reported half lives of 0.33 and 1.0 day for flubendiamide in/on tomato when used at 48 g a.i. ha −1 .…”
Section: Resultsmentioning
confidence: 96%
“…1). Kooner et al (2010) reported half lives of 0.33 and 1.0 day for flubendiamide in/on tomato when used at 48 g a.i. ha −1 .…”
Section: Resultsmentioning
confidence: 96%
“…However, the residues of flubendiamide dissipated below LOQ of 0.01 mgkg −1 after 3 and 5 days following three applications of combination mixture (flubendiamide 24% + thiacloprid 24%) 480 SC (w/v) at 48 and 96 g a.i. ha −1 on tomato and half-life values were found to range from 0.33 to 1.00 days (Kooner et al 2010). Desiodo flubendiamide was not detected in brinjal and soil at any time during the study period.…”
Section: Methods Validationmentioning
confidence: 81%
“…The concentration of FEN fell between 32 and 33 %, indicating a much faster metabolism in tomato for THC than for FEN. Previous studies with tomato established THC half-life in 2-7 days (Omirou et al 2009;Kooner et al 2010;Sharma and Parihar 2013), while in cabbage it ranged between 1.3 and 1.6 days (Wang et al 2011) and in eggplant the t 1/2 raised to 11-12 days, being dissipation rate independent of the applied dose (Saimandir et al 2009). Residues of FEN in tomato were not detectable after 3 or 7 days (Cabras et al 1985;Cabizza et al 2012) pointing to a rapid degradation rate, which is not in accordance with our results.…”
Section: Pesticides In Plantsmentioning
confidence: 94%
“…The pesticides were selected for two main reasons such that: a) they display different physicochemical characteristics, which will allow us to derive the plant uptake behaviour of organic pollutants within a broad range of properties and b) these compounds are currently used to control pests in tomato cultivation. The insecticide THC belongs to the neonicotinoid family with wide activity range including sucking insects, weevils, leaf miners and various beetle species, showing good compatibility in relevant crops (Elbert et al 2001;Omirou et al 2009;Kooner et al 2010). Fenarimol, a systemic fungicide from the group of substituted pyrimidines, is used in ornamental and horticultural crops, like tomato, in the control of powdery mildew, dollar spot, snow mould and brown patch (Cabras et al 1985;Cabizza et al 2012).…”
Section: Introductionmentioning
confidence: 99%